Implementation of the Prototype Method in Design E-Commerce New World Distro Store - Ibrahim Saleh; Ariansyah; Andi Christian (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
Distro is a place to sell clothes that is currently favored by many people. Both children and adults. This distribution itself has various types of clothing for children and adults. New World distribution provides various types of clothing such as shirts, pants, jackets, hoodies, and others. The transaction process on distros is still done manually by coming directly to the store, for that it would be better if the distro had a website as a place to sell and promote. Researchers will use the Prototype method as a development method that will be used when designing and building applications, while the research method that will be used is a descriptive method through a qualitative approach. Researchers collected data through direct observation, interviews and literature study. The design tools in this study will use the Unified Modeling Language (UML), namely, use case diagrams, class diagrams, and activity diagrams.